Nucleic acid-based electrochemical biosensors for rapid clinical diagnosis: advances, challenges, and opportunities - Hashem, Abu; Hossain, M. A. Motalib; Marlinda, Ab Rahman; Mamun, Mohammad Al; Sagadevan, Suresh; Shahnavaz, Zohreh; Simarani, Khanom; Johan, Mohd Rafie (Critical reviews in clinical laboratory sciences, 2022)
Clinical diagnostic tests should be quick, reliable, simple to perform, and affordable for diagnosis and treatment of diseases. In this regard, owing to their novel properties, biosensors have attracted the attention of scientists as well as end-users. They are efficient, stable, and relatively cheap. Biosensors have broad applications in medical diagnosis, including point-of-care (POC) monitoring, forensics, and biomedical research. The electrochemical nucleic acid (NA) biosensor, the latest invention in this field, combines the sensitivity of electroanalytical methods with the inherent bioselectivity of deoxyribonucleic acid (DNA) and ribonucleic acid (RNA). The NA biosensor exploits the affinity of single-stranded DNA/RNA for its complementary strand and is used to detect complementary sequences of NA based on hybridization. After the NA component in the sensor detects the analyte, a catalytic reaction or binding event that generates an electrical signal in the transducer ensues. Since 2000, much progress has been made in this field, but there are still numerous challenges. This critical review describes the advances, challenges, and prospects of NA-based electrochemical biosensors for clinical diagnosis. It includes the basic principles, classification, sensing enhancement strategies, and applications of biosensors as well as their advantages, limitations, and future prospects, and thus it should be useful to academics as well as industry in the improvement and application of EC NA biosensors.